A new cherry (Prunus avium) Pest in Turkey: Omaloplia labrata (Burmeister) (Coleoptera: Scarabaeidae: Sericini) - Özgen, Inanç; Ahrens, Dirk (American Entomological Society, 2018)
This study results from observations in cherry gardens in Elazi? (Turkey: Eastern Anatolia) during 2015 and 2016. In previous studies Omaloplia labrata (Burmeister, 1855) was found feeding on leaf epidermis of leaves starting from the uppermost and youngest shoots of the growth cone, causing significant damage. This pest damages trees from the first week of June to early July, and may cause significant damage if control measures are not taken. This study is the first record of this species on cherry and harming cherry trees. © 2018 American Entomological Society. All rights reserved.
Keywords: Coleoptera; New Pest; New Regional Record; Omaloplia labrata; Prunus avium; Turkey